HUBUNGAN ANTARA ANEMIA DEFISIENSI BESI DENGAN FUNGSI KOGNITIF PADA ANAK SEKOLAH DASAR USIA 09-11 TAHUN - Hening Widjayanti; Hexanto Muhartomo; M. I. Widiastuti; Amin Husni; Dani Rahmawati; Trianggoro Budisulistyo (NEURONA, 2021)
Introduction: Iron deficiency anemia is the most common form of anemia found in children. In iron deficiency anemia, levels of hemoglobin and ferritin must be considered. Hence, anemia can cause in impairment of cognitive function in children. Aim: To analyze the correlation between iron deficiency anemia and cognitive function in primary school children aged 9-11 years. Methods: This was an observational study with cross sectional design. The subjects of this study were students at Taqwiyatul Waton Primary School, Semarang and Tanjung Mas Primary School, Semarang, who met the inclusion and exclusion criteria. This study was conducted from March to June 2019. Laboratory tests for hemoglobin levels and ferritin levels were carried out at Paramitha Laboratory, Semarang. The data were obtained either from the study subjects and their parents. The assessment of cognitive function used modified Mini Mental State Examination (MMSE). Data analysis used Spearman's bivariate correlation test and partial correlation. The result was considered significant if the p value <0.05. Results: This study was carried out 70 students from Taqwiyatul Waton Primary School, Semarang and Tanjung Mas Primary School, Semarang. A moderate correlation was found between iron deficiency anemia and cognitive function (r = -0.505; p <0.001). Discussion: Their was a moderate relationship between iron deficiency anemia and cognitive function. Keyword : Cognitive function, iron deficiency anemia, nutritional status